2012
DOI: 10.1095/biolreprod.111.095596
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Regulates Mouse Fshr Promoter Activity Through an E-Box Binding Site1

Abstract: The aryl hydrocarbon receptor (AHR) mediates the toxicity of a variety of environmental chemicals. Apart from this, an understanding is emerging that the AHR has a fundamental role in female reproduction. Evidence suggests that AHR participates in regulation of follicle-stimulating hormone receptor (Fshr) transcript level in mouse ovary by binding to the promoter of this gene in vivo. The purpose of this study was to demonstrate the molecular interplay of the Fshr promoter involved in the transactivation by AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…GC differentiation and ovarian maturation was validated by measured upregulation of Fshr, Cyp19a1 , and Lhcgr (Figure 2d–f). It is known that Ahr may regulate the expression of Fshr and Cyp19a1 [19,43,68]. In our experimental setting, however, we see no prior increase in Ahr expression compared to Fshr and Cyp19a1 .…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…GC differentiation and ovarian maturation was validated by measured upregulation of Fshr, Cyp19a1 , and Lhcgr (Figure 2d–f). It is known that Ahr may regulate the expression of Fshr and Cyp19a1 [19,43,68]. In our experimental setting, however, we see no prior increase in Ahr expression compared to Fshr and Cyp19a1 .…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies have shown that the role of Ahr in the ovary may be attributed, at least partly, to regulating the expression of Cyp19a1 and thereby contributing to estradiol production [12,19]. There is also evidence that Ahr directly regulates the expression of Fshr by binding to its promoter [17,43]. According to these data, we aimed to characterize the temporal relationship between the expression of Ahr and abovementioned genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that the E-box but not USF1 is necessary for AhR binding to the FSHR promoter in vivo. AhR activates the FSHR promoter through the region from −209 to −99 bp [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These possibilities are supported by previous studies that show that AHRKO follicles have reduced mRNA expression of FSH receptors ( Fshr ) as well as a reduced number of FSH binding sites compared to WT follicles [5,8]. Further, they are supported by studies indicating that the AHR and FSH pathways may interact to regulate transcription of the Fshr because the AHR binds to aryl hydrocarbon response elements in the promoter regions of the Fshr and an E-box binding site in the mouse ovary [5,11]. …”
Section: Introductionmentioning
confidence: 99%